Promoting Islamic Religiosity in Connection with Local Cultures and the Nation of Indonesia in Higher Education - Hakam, Ahmad; Anggraeni, Dewi; Hadiyanto, Andy; Muminova, Zarina (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to investigate how religion (Islam) is understood, confessed, and practiced in a way that it interacts positively with local cultures and the concept of nation as a uniting factor of the people in Indonesia. This research uses a qualitative method by reviewing relevant literature, conducting observation, and interviews with informants in various higher education institutions on Java Island. Data were taken from Islamic Religious Education (IRE) or Pendidikan Agama Islam (PAI) course, interview with students and lecturers, as well as the course’s accompanying programs administered by public and private universities in Java. The results of the study show that Islamic religiosity and appreciation of local cultures within the frame of Indonesia as a nation can go hand in hand. This mindset is achieved through a religious education course and its extra or co-curricular programs at universities in Indonesia, which is in line with the agenda of building the nation through being religious and maintaining harmony in diverse Indonesian society.